Diverging Driver Performance along Deceleration Lanes: Driving Simulator Study. Issue 1 (January 2015) - Calvi, Alessandro; Bella, Francesco; D'Amico, Fabrizio
Highway diverge areas are often characterized by high crash rates. Worldwide, geometric design guidelines propose deceleration lanes with a parallel or tapered layout to promote a free-vehicle condition, while the guidelines neglect the potential effects of traffic flow and risky driving behaviors that are induced by the wrong perceptions of road geometry and vehicle interference. A driving simulation study was conducted to analyze the effects of traffic flow and deceleration lane geometry on the driving performance of diverging drivers. Two types of deceleration lanes (parallel and tapered) were implemented in a simulator, and two traffic conditions (low and high traffic flows) were simulated for each type of lane. Thirty-one drivers took part in the experiments. The effects of traffic flow on driving performance while drivers approached the diverge area and during their deceleration were investigated. The study found that lane type significantly affected the speeds of diverging drivers, independent of traffic conditions, with greater interference with the through traffic on the tapered lane. Traffic conditions were found to influence the driver's trajectory along the tapered lane, and this trajectory delayed the exiting maneuver under heavy traffic conditions. This effect was not found to have been significant for parallel deceleration lanes on which the deceleration rates were significantly affected by traffic conditions: higher decelerations were recorded under light traffic conditions. No significant traffic effects on deceleration rates were found on the tapered lane.